Improving the equity component of the Lagos State Land Use Charge (2018) for enhanced property tax yields / Gabriel Kayode Babawale - Babawale, Gabriel Kayode (Faculty of Architecture, Planning and Surveying, 2019)
Property tax has remained a subject of recurrent debate amongst policy makers, scholars, public officials, real estate valuers, and other stakeholders, virtually everywhere over the years. The contention centres on issues such as the tax base, tax incidence, efficiency, and particularly, equity or fairness, among others. Qualities like ease of collection, difficulty of avoidance, accountability, and transparency etc., that ordinarily mark out property tax as a good tax in principle, are often compromised by controversial policies and mal-administration, particularly the latter. The new Lagos State Land Use Charge2018 (LUC, 2018) came into force effective January, 2018. Ina similar version that its immediate predecessor, the Land Use Charge2001 (LUC, 2001), attracted spontaneous and widespread protests on promulgation, the criticisms and protests that greeted the passage LUC (2018)has been vehement and remained unabated until the government was forced, like it did with the erstwhile law, to succumb to substantial but arbitrary reductions in rates and allowances across board (at two different times to date) but without a formal amendment to the law; an exact replica of what transpired under the erstwhile law and which opened it to abuse and arbitrary implementation with its compliance and revenue yields implications. The last of these reductions which took place in August saw a whopping 50%, and 25% cut in assessed rates on commercial properties and industrial properties, respectively. This study employed the doctrinal research methodology whereby the valuation or assessment aspect of the LUC (2018) was diagnosed with a view to finding amicable resolutions to the equity problem that virtually crippled the effectiveness of LUC (2001) over its seventeen years of existence and is already threatening the survival of the new LUC (2018).